PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Iwan Satibi; Firman Bayu Asmara (e-JKPP, 2023)
Aim of research is to examine (1) effect of motivation on employee performance in R&D agency in Bandung, (2) effect of work discipline on employee performance in R&D agency in Bandung, and (3) combined effect of motivation and work discipline on employee performance in R&D agency in Bandung. Quantitative methods are used in this research. The subjects of this study were 50 employees of the Regional Development Planning, Research and Development Agency of the Regency of Bandung. Data was collected by means of questionnaires and analysis was done by means of different linear techniques. The results of this study are (1) if calculation result of t count 7.745> t table value 2.012, Ha is accepted, (2) if calculation result of t count 8.050> t table value 2.2012, Ha is accepted. So it can be concluded that work discipline affects the performance of employees and (3) from the hypothesis test where Sig F is obtained at 0.000 <0.05 with F count (65.895) > F table (3.196), then Ha is accepted. To conclude, motivation and work discipline together affect employee performance in Bandung Regency